Assessing the effectiveness of mindfulness-based programs on mental health during pregnancy and early motherhood - a randomized control trial - Wan-Lin Pan; Chiung-Wen Chang; Shin-Ming Chen; Meei-Ling Gau (BMC, 2019)
Abstract Background The process of entering motherhood is highly stressful for women, with 15-85% of new mothers experiencing postpartum blues or depression. This study was designed to evaluate the efficacy of a mindfulness-based childbirth and parenting program in improving psychological health during the postpartum period. Methods This research was a randomized controlled trial with single blinding. Recruitment began after the participating hospital granted formal approval. A total of 74 women between 13 and 28-weeks gestation were allocated either to the intervention group or to the comparison group. The intervention program included a series of eight, 3-h classes held once weekly and 1 day of 7-h silent meditation. Psychological health was assessed at baseline and 3-months postpartum. Results Significant differences in stress and depression were observed in both groups over time. Stress scores and depression scores were significantly better in the intervention group than in the comparison group at 3-months postpartum (F = 7.19, p = .009 and F = 7.36, p = .008, respectively). No significant difference between the groups was identified for mindfulness scores at 3-months postpartum. Conclusions The intervention program effectively reduced postpartum self-perceived stress and depression, suggesting that this program provides acceptable and long-term benefits to women during pregnancy and the postpartum period. The teaching and practice of mindfulness meditation and parenting education during pregnancy may help reduce stress and depression in pregnant women as they transition into parenthood. Trial registration The ClinicalTrials.gov identifier for this study is: NCT03185910. The study was retrospectively registered on 14 June 2017.